THE DYNAMICS OF ISLAMIC MICROFINANCE AWARENESS AND FINANCIAL LITERACY - Nosheen, Safia; Iqbal, Javed; Yasser, Farah; Ali, Dr. Muhammad Kashif (Journal of Management and Islamic Finance, 2024)
This study seeks to bridge the existing gap in the literature, offering a comprehensive analysis of the relationships among Islamic Microfinance Awareness, Financial Literacy, Trust in Financial Institutions, and Customer Access to Islamic Microfinance Products. Small enterprises have been targeted as a sample of Lahore city, Pakistan's second-largest city in terms of population and economic significance. The data is gathered through questionnaires and 256 responses collected from employees across diverse organizations, reinforcing the study's credibility. Partial Least Squares Structural Equation Modelling (PLS-SEM) used to achieve research goals. The study's results align with all the specified hypotheses, confirming the proposed relationships and shedding light on the interconnected dynamics between Islamic Microfinance Awareness, Financial Literacy, Trust in Financial Institutions, and Customer Access to Islamic Microfinance Products. This study investigates the lesser-known aspect of Islamic Microfinance Awareness, providing insights into its influence on consumer access and trust. The practical implications are outlined, proposing that policymakers and financial institutions implement targeted awareness campaigns and financial education initiatives. The research culminates in valuable recommendations for relevant parties, emphasizing the significance of establishing the confidence to promote increased consumer involvement with Islamic Microfinance offerings.